Sei sulla pagina 1di 172

 

 

 

 

 

 

 

 

 

P P F F F F F F F \ F F

c : F −→ R

F

(P )

min{c(x) : x F }.

P z(P ) x F c(x ) = z(P ) P x F

c(x ) c(x)

x F.

(P )

max{−c(x) : x F },

z(P ) = z(P ) c(x) F c(x) F P P F x F F F F x F x F F F 0 F 1 (P) N P

F k = {x F : c(x) k},

k k

k k

P

¯

¯

( P )

¯

min{c¯(x) : x F}

¯

F F c¯(x) c(x)

P P c P F

x F P

¯

P

¯

P z( P) z(P)

c¯(x)

c(x)

P z( P) z(P)

x F

¯

P p P p P p p

P p A P A p A p A P g(n) n

g(n) n g(n) g(n) n g(n) f (x) g(x)

g(x) O(f (x)) c 1 c 2

g(x) c 1 f(x) + c 2

x

g(x) Ω(f (x)) f (x) O(g(x))

g(x) Θ(f (x)) g(x) O(f (x)) Ω(f (x))

g(x) A x P A O(f (x)) g(x) O(f (x)) Ω(f (x)) g(x) Ω(g(x)) Θ(f (x)) g(x) Θ(f (x)) O(x k ) k x b l l b O(x k b l )

O(p(x)) p(x) x

N P N P x

N P N P P N

N P

N P P P

P ⊆ N P N P P P = N P P = N P

P Q A Q Q P Q P Q P

A Q P Q

A A

A B B C

A C

A B

A

∈ P ⇒ B

P

A B

B ∈ P

A ∈ P

N P A N P A ∈ N P B ∈ N P B A N P N P N P N P P = N P N P N P P = N P N P N P N P N P N P N P N P P = N P N P N P P = N P N P

N P

P F R n F

g(x) b g R n

, m,

b R m g i : R n R, i = 1, F

F = {x R n : g i b i , i = 1,

, m}.

min{c(x) : g i b i , i = 1,

, m},

c(x) g i

x

P N P

n x i

f(x) = c T x = c 1 x 1 + c 2 x 2 +

+ c n x n =

n

i=1

c i x i ,

c R n x R n

ax = b ax b ax b a R n b R

max{c T x : Ax b, x 0},

A m × n b R m m c x Ax b, x 0

x

R n R n R n

x c

n x i

f (x) = c T x c R n x Z

ax = b ax b ax b a R n b R

max{c T x : Ax b, x 0, x Z},

A m × n b R m m

A

max{c T x : Ax b, x 0, x Z}

max{c T x : Ax b, x 0}.

Ax b P P n n 2 n

Ax b P P

min{c T x : Ax = b, x 0, x Z}

P = {x : Ax = b, x 0},

x arg min{c T x : x P}.

x

x

j

x

min{c T x : x P Z ({x : x j x

j

} ∪ {x : x j x })}.

j

min{c T x : x P, x x

j

, x Z}

min{c T x : x P, x x

j

, x Z},

z z z

max{c T x : Ax b, x 0, x Z}.

P I = {x : Ax b, x 0, x Z}

Ax b

P 0 = {x : Ax b, x 0}

Ax b P 0 P I P I P 0 P I P 0 P gx h P P x P gx = h P a i

, m

A b i b i = 1,

a T x b i

y 1 ,

gx h g

P I Ax b h gx h P 0

i

, y m g = m

i=1 y i a i h = m

i=1 y i b i

P 1 = {P 0 (gx h )}

gx h P 0 g P 1 P 0 P 0 P I P 1 P 0 P 1 P I P 0 P 1 P 0 P I k P k = P I P 0 A b P 0 P I P 0

z = c 0 +

j∈N

x i = b i

j∈N

c j x j

a ij x j

a ij N

x i + a ij x j b i

j∈N

a ij f ij = a ij a ij b i b i = f i

j∈N

a ij x j a ij x j b i b i

j∈N

j∈N a ij a ij x j b i b i

f ij x j ≤ −f i

j∈N

j∈N

f ij x j f i .

b i f i

x j = 0 x j

j∈N

j∈N

f ij x j = 0.

f ij x j f i

P I f ij 0 x j 0 f ij x j 0

f ij x j 0.

j∈N

x i +

j∈N

a ij x j = b i

x i + a ij x j b i .

j∈N

x i + a ij x j b i .

j∈N

min{f (x) : g i (x) 0, i = 1,

, m, x F R n },

x R n F f : F −→ R g i : R n −→ R g i (x) 0

L(λ) = min f(x)

m

i=1

λ i g i (x) : x F

λ λ i λ 0. L(λ) g i (x) 0. x g i (x) 0

f(x)

m

i=1

λ i g i (x) f(x)

λ i λ

min{f (x) : h i (x) = 0, i = 1,

, l, x F },

h i (x)

min f(x)

l

i=1

λ i h i (x) : x F

λ i

λ 0 x

(λ ) T g(x ) = 0,

x λ D = max L(λ)

x λ 0

L(λ) = min f(x)

xF

m

i=1

λ i g i (x) f(x ).

L(λ ) = f(x )

x

λ

min{c T x : x P Z n },

P = {x R n : Ax b, x ∈ Q}

Q

z PL = min{c T x : x P}

z DL = max min

λ0

xQZ n c T x + λ T (b Ax) .

z

PL z

DL ,

(Q ∩ Z n ) = Q

z

PL = z

DL .

Q

DL

z PL = z

(P )

min{c T x : Ax = b, Dx d, x 0}

Ax = b P

(P